The Awareness of Rare Diseases Among Medical Students and Practicing Physicians in the Republic of Kazakhstan. An Exploratory Study - Walkowiak, Dariusz; Bokayeva, Kamila; Miraleyeva, Alua; Domaradzki, Jan (Frontiers in Public Health, 2022)
Although national plans or strategies for rare diseases (RDs) have been implemented in many jurisdictions research show that one of the main barriers RD patients face during medical encounter is medical professionals' low level of knowledge and experience on the diagnosis, treatment and rehabilitation of RD patients. Consequently, there is a need to increase the standards of medical education in the field of RDs and to revise the undergraduate and postgraduate training programs. However, while studies on medical education in the field of RDs has been conducted in various countries across the both Americas, Asia or the European Union, still little is known about the awareness of RDs among healthcare professionals in the Republic of Kazakhstan. Thus, we conducted a survey among 207 medical students and 101 medical doctors from the West Kazakhstan Marat Ospanov Medical University, Aktobe, Kazakhstan. The study was conducted between March and May 2021. The questionnaire assessed their knowledge about the number, examples, etiology and estimated frequency of RDs. It also evaluated respondents self-assessment of competence in RDs. Although the majority of respondents agreed that RDs constitute a serious public health issue both medical students and medical doctors showed insufficient knowledge on the etiology, epidemiology and prevalence of RDs, and many had problems with separating RDs from more common disorders. Moreover, they also lacked knowledge about and the central register of RD patients and reimbursement of orphan drugs in Kazakhstan. Finally, while almost half respondents declared having had classes about RDs during their studies most perceived their knowledge about RDs as insufficient or poor and felt unprepared for caring for RD patients. Additionally, although majority of respondents in both groups believed that all physicians, regardless of their specialization, should possess knowledge on RDs many respondents did not look for such information at all.